2016
DOI: 10.1007/s10068-016-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-adipogenic activities of acorn shells

Abstract: Antioxidant and anti-adipogenic activities of water extract (WE) and methanol extract (ME) of acorn shells (AS), from Carruth. grown in Korea, were investigated. At a concentration of 50 μg/mL, the WE had a scavenging activity of 53.84% for the DPPH and 76.09% for the ABTS radical, while the ME had corresponding scavenging activities of 29.09 and 48.43%. Total phenolic contents of WE and ME were 375.96 and 288.01 mg gallic acid equivalents/g of extracts, respectively. Both extracts significantly inhibited 3T3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…1, AS presented the highest antioxidant activity, followed by unleached acorn nuts and finally AF. The antioxidant potency of acorn shells has been also reported by Youn et al [26], where the examined polar extracts (of lower concentration) presented similar with the present study % DPPH inhibition values. The 60% of the initial antioxidant activity of acorn nut (UAN) is lost during the leaching procedure for the preparation of edible flour.…”
Section: Antioxidant Activity Of Acorn Materialssupporting
confidence: 91%
See 1 more Smart Citation
“…1, AS presented the highest antioxidant activity, followed by unleached acorn nuts and finally AF. The antioxidant potency of acorn shells has been also reported by Youn et al [26], where the examined polar extracts (of lower concentration) presented similar with the present study % DPPH inhibition values. The 60% of the initial antioxidant activity of acorn nut (UAN) is lost during the leaching procedure for the preparation of edible flour.…”
Section: Antioxidant Activity Of Acorn Materialssupporting
confidence: 91%
“…Finally, the acorn shells (AS) which is a by product, contained 38.7 ± 0.8 mg GAE/g dry shell, implying its potency for efficient exploitation as phenol source. Cantos et al [1] also reported that in Q. suber, the contribution of skin to TP content was relatively high, whereas acorn shell extracts from Q. acutissima Carruth have been also reported to be a good phenolic and antioxidant source [26].…”
Section: Phenolic Content Of Acorn Materialsmentioning
confidence: 99%
“…This is due to the fact that during the heat treatment, the tannins that are found in a fairly high amount in the raw acorn degrade, and thus increase the content of non-tannin phenolic compounds, especially gallic acid. In order to obtain a more complete view, the results obtained were correlated with those obtained by Youn et al, who obtained values between 375.96 (water extract) and 288.01 mg GAE/g (methanol extract) for acorns of Quercus acutissima Carruth [49]. Ranjbar Nedamani et al obtained different results for oak fruits (Quercus branti) of 22.64 g of gallic acid per 100 g (methanol extract / dry weight) [50] compared to us, and Khanav et al obtained results of up to 88.43 GAE/100 g (water:methanol extract) [51].…”
Section: Total Polyphenol Content Of Roasted Acorn Powdermentioning
confidence: 58%
“…Similarly, chestnut shells have been reported to contain high amounts of phenolics, with the TPC of the WE and ME being 55.8 and 32.5 g GAE/100 g extract, respectively [15]. Acorn shells have also been reported to contain high amounts of phenolics, with the TPC of the WE and ME being 375.96 and 288.01 mg GAE/g extract, respectively [16]. The antioxidant activity of CCT extracts was evaluated by estimating their free radical scavenging activity (RSA).…”
Section: Resultsmentioning
confidence: 99%